2018
DOI: 10.1148/radiol.2018180249
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided Cryoablation for Sporadic Renal Cell Carcinoma: Three- and 5-year Outcomes in 220 Patients with Biopsy-proven Renal Cell Carcinoma

Abstract: Purpose To evaluate the long-term efficacy of image-guided cryoablation of sporadic clinical T1 (cT1) biopsy-proven renal cell carcinoma (RCC) and the technical success and safety of all cryoablation treatments. Materials and Methods For this retrospective single-institution study, 433 patients (median age, 68 years; range, 19-90 years), of whom 293 were men (median age, 69 years; range, 19-90 years) and 140 were women (median age, 68 years; range, 30-89 years), who had 484 cT1 renal masses (mean size, 33 mm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
54
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 32 publications
14
54
4
1
Order By: Relevance
“…Seventeen articles including 2,320 lesions treated with CRA were identified (►Table 3). 48,[63][64][65][66][67][68][69][70][71][72][73][74][75] Average size was 2.6 cm, and percutaneous (10), laparoscopic (7), and both percutaneous and laparoscopic (1) approaches were included. Overall recurrence rate was 8.1% (189 lesions) with recurrence rates of 6.4 and 12.3% for percutaneous and laparoscopic approaches, respectively.…”
Section: Review Of Contemporary Oncologic Outcomesmentioning
confidence: 99%
“…Seventeen articles including 2,320 lesions treated with CRA were identified (►Table 3). 48,[63][64][65][66][67][68][69][70][71][72][73][74][75] Average size was 2.6 cm, and percutaneous (10), laparoscopic (7), and both percutaneous and laparoscopic (1) approaches were included. Overall recurrence rate was 8.1% (189 lesions) with recurrence rates of 6.4 and 12.3% for percutaneous and laparoscopic approaches, respectively.…”
Section: Review Of Contemporary Oncologic Outcomesmentioning
confidence: 99%
“…A recent study showed similar recurrence-free survival outcomes for PN and cryoablation for sporadic cT1b renal tumors (4-7 cm) [8]. However, few studies of cryoablation for cT1b tumors are available [9][10][11]. Atwell et al evaluated percutaneous cryoablation of 46 T1b renal tumors, with 15.2% of major complications, and 96.4% progression-free survival at 1-, 3and 5-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…n this issue of Radiology, Breen et al (1) publish their longterm oncologic and safety findings after image-guided percutaneous cryoablation (CRA) for stage 1a (,4 cm) and stage 1b (4 -7 cm) renal cell carcinoma (RCC). The rather distinct natural history and biologic behavior of RCC-relative to those of most other epidemiologically significant human malignancies-commands a correspondingly unique posture toward imaging diagnosis and treatment.…”
mentioning
confidence: 99%